Turbo multiuser detection for MC-CDMA signals with strongly nonlinear transmitters - Silva, Paulo (2013)
In this paper we consider the uplink transmission in MC-CDMA (multicarrier -coded division multiple access) systems. Since MC-CDMA signals are OFDM-like multicarrier signals, they have high envelope fluctuations and a high PMEPR (Peak-to-Mean Envelope Power Ratio) which leads to amplification difficulties. To reduce the envelope fluctuations of the transmitted signals, while maintaining the spectral efficiency, the MC-CDMA signal associated to each MT (mobile terminal) is submitted to a clipping device, followed by a frequency-domain filtering operation. However, the nonlinear distortion effects can be high when an MC-CDMA transmitter with reduced envelope fluctuations is intended. In this paper, we define an iterative receiver that jointly performs a turbo-MUD (Multiuser Detection) and the estimation and cancellation of the nonlinear distortion effects. The set of simulation results presented shows that the proposed receiver structure allows good performances, very close to the linear receiver ones, even for high system load and/or when a low-PMEPR is intended for each MT.